HUBUNGAN POLA ASUH ORANG TUA DENGAN PERILAKU SOSIOPATIK PADA SISWA SMPN 1 BULANGO TIMUR KECAMATAN BULANGO TIMUR KABUPATEN BONE BOLANGO - Nur Uyuun I. Biahimo; Dewi Modjo (-, 2021)
This research was conducted at SMPN 1 Bulango Timur. The objective is to obtain the relationship between parenting parents with sociopathics on students at SMPN 1 Bulango Timur. The design used observational analytic with cross sectional approach. The samples are 55 students which determine through purposive sampling technique. Collecting data used questionnaire. Analysis data used statistical Chi Square test. The result showed parenting of students parents at SMPN 1 Bulango Timur most of it is democratized there are 41,7% and 39,6% has easy sociopathics. There is relationship between parenting of parents with sociopathics on students at SMPN 1 Bulango Timur, Bulango Timur sub district Bone Bolango distrct (p value 0,000).